Stratigraphy of the Albian-Cenomanian boundary interval in the Agadir Basin, Morocco: ammonites, microcrinoides, planktonic foraminifera - Andrew Scott Gale; William James Kennedy; Maria Rose Petrizzo (Acta Geologica Polonica, 2021)
Gale, A.S., Kennedy, W.J. and Petrizzo, M.R. 2021. Stratigraphy of the Albian-Cenomanian boundary interval in the Agadir Basin, Morocco: ammonites, microcrinoids, planktonic foraminifera. Acta Geologica Polonica, 71 (4), 453-480. Warszawa. The uppermost Albian and lowermost Cenomanian succession at Abouda Plage, north of Agadir, in the Agadir Basin, western Morocco, is described in detail, and ammonites, microcrinoids and planktonic foraminifera are recorded and illustrated. The lower part of the Alt Lamine Formation yields ammonites indicative of the Pervinquieria (Subschloenbachia) rostrata and P. (S.) perinflata ammonite zones, and the Thalmanninella appenninica planktonic foraminiferan Zone. The base of the Cenomanian is identified at 42.2 m above the base of the Alt Lamine Formation, based on the lowest occurrence of the planktonic foraminiferan Thalmanninella globotruncanoides Sigal, 1948. Lower Cenomanian ammonites of the Graysonites adkinsi Zone enter 3 m higher in the succession. Microcrinoid zones AlR11 and AlR12 are identified in the Upper Albian, and the base of the CeR1 Zone coincides with the lowest occurrence of Cenomanian ammonites. The ammonite and microcrinoid occurrences and detailed distributions are very similar to those found in north central Texas, which, in the Cenomanian, was 5,300 km to the west. The new records suggest that the G. adkinsi Zone is equivalent to the uppermost (Lower Cenomanian) part of the Pleurohoplites briacensis Zone of the Global Stratotype Section for the base of the Cenomanian stage. An hiatus, of global extent, immediately underlies the base of the G. adkinsi Zone and is represented in the Agadir Basin by an erosion surface containing bored and encrusted hiatus concretions.